Breast metastases from oligodendroglioma: An unusual extraneural spread in two young women and a review of the literature - Mazza, E.; Belli, C.; Terreni, M.; Doglioni, C.; Losio, C.; Cantore, M.; Mambrini, A.; Reni, M. (Critical reviews in oncology/hematology, 2013)
Extraneural dissemination of oligodendroglioma is rare. Cases of breast metastases have never been described in the literature. We report the first two cases of young women with initial diagnosis of anaplastic oligodendroglioma who experienced mammary gland metastases and a review of the literature. Immunohistochemical analysis performed on material from both primary and metastatic sites did not allow to draw any conclusion on possible etiopathogenetic hypothesis. A review of literature yielded 35 cases of extracranial metastatic oligodendroglioma from 1989 to 2012. Though rare, extracranial dissemination from oligodendroglioma may occur not only in long surviving heavily pre-treated patients. The review of literature and these two cases suggest that spread is primarily to bone and then from bone to other organs through hematogenous route mostly due to leptomeningeal or dura mater invasion. Chemotherapy regimens similar to those commonly used for non metastatic oligodendroglioma are recommended for patients with good performance status.